PRZYGOTOWANIE DO TWÓRCZOŚCI PEDAGOGICZNEJ W KSZTAŁCENIU WSTĘPNYM NAUCZYCIELI JĘZYKÓW OBCYCH - Jastrzębska, Elżbieta (Neofilolog, 2019)
Creativity in teaching in the subject literature can be divided into three categories: the creative process, the product and the support of the development of creative activity in students. Not only is creativity important for the teacher today but also it is an essential part of his or her professional identity. In XXI century pedeutology [a branch of educational theory] the vision is of an open-minded and autonmous teacher, a reflective practitioner who is prepared to create his or her own new strategies to function in educational situations which are constantly changing. This educator effectively supports the personal development of the student and their process of learning. For this reason, creativity in teaching should also be one of the principal objectives of the professional training of the foreign language teachers, which in turn poses important questions. The notion of creativity in teaching, its scope and how it can be prepared for during the aca-demic training of the foreign language teachers are the subjects of the article.